Development and Usability Testing of a Finger Grip Enhancer for the Elderly - Tan D.W.H.; Ng P.K.; Noor E.E.M.; Saptari A.; Hue C.C.; Ng Y.J. (MDPI, 2023)
As people age, their finger function deteriorates due to muscle, nerve, and brain degener-ation. While exercises might delay this deterioration, an invention that enhances elderly peoples pinching abilities is essential. This study aims to design and develop a finger grip enhancer that facilitates the day-to-day pinching activities of elderly people. This research is an extension of a previous study that conceptualised a finger grip enhancer. The device facilitates finger flexion on the thumb and index finger, and weighs 520 g, allowing for improved portability and sufficient force exertion (13.9 N) for day-to-day pinching. To test for usability, eleven subjects aged 65 years and above performed a pinch-lift-hold test on various household objects. The pinch force before and after utilising the device was measured. Using Minitab 18, the statistical significance of using this device was analysed with a paired-samples t-test. With this device, the elderly peoples pinching abilities significantly improved in both pinch force and pinch force steadiness (p < 0.05). The proposed device has the potential to enhance elderly peoples quality of life by supporting a firm pinch in the handling of everyday objects. This research has applicational value in developing exoskeleton devices for patients who require rehabilitation. 2021 by the authors. Licensee MDPI, Basel, Switzerland.